Analisa Proses Produksi Bracket Suspensi Bp-018 - Restian Khafi Nurhendi; Agus Wibowo (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The production process in general is the process of transforming raw materials into finished products. A process is considered effective if it does not result in waste. This study aims to analyze the production process of the BP-018 suspension bracket and identify the issues occurring during its production. The methods used in this research include direct observation, data collection on the production process, and documentation of the work process. The analysis results show that there are several factors causing the ineffectiveness of the production process, including an imbalanced processing time, suboptimal use of machinery, and product defects due to operator errors. Keywords: suspension bracket, production process, product quality Abstrak Proses produksi secara umum merupakan proses pengolahan bahan baku menjadi produk jadi. Suatu proses dikatakan efektif jika dalam proses tersebut tidak menghasilkan pemborosan. penelitian ini bertujuan untuk menganalisa proses produksi bracket suspensi Bp-018, serta mengidentifikasi permasalahan yang terjadi dalam proses produksinya. Metode yang digunakan dalam penelitian ini meliputi observasi langsung, pengumpulan data proses produksi, dokumentasi proses kerja. Hasil analisa menunjukkan bahwa terdapat beberapa faktor yang menyebabkan ketidakefektifan proses produksi, antara lain waktu proses yang tidak seimbang, penggunaan mesin yang kurang optimal, serta adanya cacat produk akibat kesalahan operator. Kata Kunci: bracket suspensi, proses produksi, kualitas produk